Avaliação do potencial tóxico do inseticida Clorantraniliprole e do herbicida Ametrina, isolados e em mistura, em diferentes temperaturas para uma espécie zooplanctônica - Lucca, Gisele Maria de (2021)
The objective of this research was to evaluate the effects of the pesticides Chlorantraniliprole and Ametryn, isolated and mixed, on the species Ceriodaphnia silvestrii at two different temperatures and thus, carry out a preliminary risk assessment of these pesticides to Brazilian water bodies. However, comparative tests of the acute and chronic effects of isolated and mixed compounds were carried out with their standard formulation. The results demonstrated that the acute toxicity tests pointed an increase in mortality with increasing exposure time according to the selected compounds. Concerning to the chronic toxicity tests, the herbicide Ametryn significantly reduced the fertility of C. silvestrii females at concentrations from 20 μg L-1 and the insecticide Chlorantraniliprole caused hormetic effects on female fertility in the two lowest concentrations tested (0,02 and 0,04 μg L-1) and significantly reduced reproduction at the concentration of 0,14 μg L-1. In the experiments, combining the methodology of standardized tests using three temperatures (17, 23 and 30°C), the tests were carried out with the cladoceran C. silvestrii after the acclimation period. In acute toxicity tests for the insecticide Chlorantraniliprole, significant effects on the immobility of organisms were observed at low concentrations tested. In chronic tests, there was a hormesis effect at the temperature of 23°C for the concentration of 0,04 μg L-1 and significant reduction in female fertility were found for body length, number of eggs and offspring from the concentration of 0,07 μg L-1 at the three temperatures tested. For the herbicide Ametryn, the results of the acute tests showed a significant effect of temperature on the toxicity of the herbicide Ametryn, at the highest temperature tested (30°C), the average mortality occurred at lower concentrations than when compared to the mean mortality of the lower temperatures (17 and 23°C). In chronic tests, significant reductions were observed in the following parameters: body length, number of eggs and newborns, with emphasis on the temperature of 17°C, where the organisms of C. silvestrii were more sensitive than at the temperatures of 23 and 30°C. Thus, our results show that acclimation can generate significant differences in the toxicity and distribution of the sensitivity of the cladoceran C. silvestrii, indicating the need to incorporate the thermal factor in ecotoxicity tests with tropical aquatic organisms, as well as this environment variable influences biological processes of that species. In the tests with the mixture, in the acute toxicity tests of the active ingredients, the data showed dependent interaction on the dose level from the Addition of Concentration model (CA), with antagonism occurring at low doses and at high doses what was observed was synergism between its components. Chronic exposure also resulted in a dose-dependent toxicity, with antagonism occurring at low doses and synergism at high doses with a change in interaction occurring at a level equal to EC50. Given the above, it is concluded that the pesticides studied, isolated, in mixture and with acclimation at different temperatures caused toxicity in the test organism, representing potential risks to aquatic environments, suggesting more restrictive measures for the use of these compounds to ensure greater protection of freshwater bodies in tropical environments.